Literacy for All in 100 Days? A Research-based Strategy for Fast Progress in Low-income Countries - Abadzi, Helen (World Bank, Washington, DC, 2013)
In low-income countries many students are marginalized very early and remain illiterate. In grades 1-3 they attend rarely, though they may officially drop out in grade 4. Many others graduate from primary school without having learned letter values. The worrisome outcomes, despite much donor investment in low-income countries, have prompted scrutiny of the methods, and textbooks used to make students literate. This document offers insights from cognitive neuroscience and evidence suggesting that students can be taught basic literacy within the first semester of grade 1, if taught in consistently spelled languages. Teaching students at risk of dropout to read as early as possible enhances equity. However, the reading methods used in many countries are complex and hard for teachers to execute. They pertain to high-income countries and to certain western European languages. English but also French, Portuguese, and Dutch have complex spelling systems. English in particular requires three years of learning time. (French requires about two). Reading instruction for English is expensive and complex. Lists of whole words must be learned, vocabulary and early training in predictions are needed in order to make sense of words that cannot be sounded out. Learning must be started at kindergarten, parents must help at home, and many weaker students require remedial instruction. Since English is an official language in many countries, the travails of learning to read in this language have been considered the normal fate of reading. Overall, reading methods must be resilient to the vicissitudes of implementation. Many activities work well in higher-income countries or small pilots, but at scale-up they sink. Governments and donors should train up to existing capacity, rather than try to raise capacity to the requirements of complex methods.